2023
DOI: 10.3389/fpsyt.2023.1234553
|View full text |Cite
|
Sign up to set email alerts
|

The association between socioeconomic status and health-related quality of life among young and middle-aged maintenance hemodialysis patients: multiple mediation modeling

Qingxin Mai,
Siyi Xu,
Jingyi Hu
et al.

Abstract: ObjectiveTo explore the relationship between socioeconomic status (SES), illness perception, social functioning, and health-related quality of life (HRQoL) of young and middle-aged maintenance hemodialysis (MHD) patients and the internal mechanism of action.DesignA multicenter cross-sectional study.MethodsAn aggregate of 332 young and middle-aged MHD patients were enrolled from hemodialysis centers in four general hospitals in Guangzhou, Guangdong, China, from June to December 2022. The questionnaires used inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 73 publications
0
2
0
Order By: Relevance
“…Item 9 of the questionnaire entailed an open-ended inquiry, wherein patients were prompted to pinpoint the three most substantial factors contributing to their illness. Widely used in the MHD patients, this scale has demonstrated a Cronbach’s alpha coefficient of 0.757 [ 39 ]. In the present study, the scale demonstrated a Cronbach’s α coefficient of 0.829, indicating good internal consistency.…”
Section: Methodsmentioning
confidence: 99%
“…Item 9 of the questionnaire entailed an open-ended inquiry, wherein patients were prompted to pinpoint the three most substantial factors contributing to their illness. Widely used in the MHD patients, this scale has demonstrated a Cronbach’s alpha coefficient of 0.757 [ 39 ]. In the present study, the scale demonstrated a Cronbach’s α coefficient of 0.829, indicating good internal consistency.…”
Section: Methodsmentioning
confidence: 99%
“…14 The level of HRQoL is important in clinical decisionmaking and has been considered an important predictor of mortality and mobility. 15 With increasing age, various physiological functions of the human body gradually decline, thereby reducing the mobility and self-care abilities of olderadult inpatients. They also experience physical and mental damage caused by chronic diseases, which can lead to a decline in HRQoL.…”
Section: Introductionmentioning
confidence: 99%